Protein enrichment of cassava peel by submerged fermentation with trichoderma viride (ATCC 36316) (2010)
"Cassava (Manihot esculenta Crantz) peel is one of the solid wastes produced as a consequence of cassava processing. It is low in protein but contains a large amount of carbohydrate, causing an environmental problem with disposal. In order to add-value to this major cassava processing waste and also reduce its resultant environmental pollution, this study investigated the effect of submerged fermentation using Trichoderma viride ATCC 36316 on the protein content and amino acid profile of enzyme and non-enzyme pre-treated cassava peel. Compositional analysis of the product obtained with T. viride in the fermentor revealed that dry biomass increased in crude protein, true protein, crude fat, crude fibre, ash and total dietary fibre. The crude protein increased from 4.21 to 37.63 and 36.52% for enzyme and non-enzyme pre-treated fermented samples respectively with 31.6% as true protein for the former and 29.03% as true protein for the latter while the starch contents reduced considerably in both samples. Starch reduction was from 51.93 to 24.34 and 26.07% for enzyme and non-enzyme pre-treated fermented samples, respectively. The fermented products contained all the essential amino acids; however the chemical score of essential amino acids indicated methionine as the limiting amino acid. "